A study of paediatric empyema thoracis presentation in a tertiary care hospital in Visakhapatnam, India - Prasada Rao, M. Surya; Chandra, P. Satish (International Journal of Contemporary Pediatrics, 2018)
Background: Empyema thoracis is an accumulation of pus in the pleural space. The incidence of empyema in children is increasing. Adequate knowledge of treatment modalities is therefore essential for every pediatrician. Pediatric empyema thoracis is a complication of bacterial pneumonia, prevalence of empyema is predominant inspite of advent newer antibiotics still resulting in significant morbidity and mortality which attributes to the poverty, ignorance, illiteracy, and poor compliance to therapy. The objective of this study was to study the age-sex profile, clinical presentation, etiologic agents, management and the overall treatment outcome of empyema thoracis in children. Methods: This was a prospective observational study, conducted in the Department of Pediatrics, King George Hospital, Visakhapatnam, from November 2014 to December 2016. All children in age group of 0 to 12 years diagnosed pyogenic empyema during the study period were included in the present study. In the present study 72 children was found to be having empyema. Results: Majority of patients (58.32%) were seen in age group of 1-5 years. Fever (100%), breathlessness (94.44%), and cough (97.22%) were the commonest presenting features. Bacteriological examination revealed staphylococcus aureus as the commonest etiologic agent (16.66%) isolated from pleural fluid culture. All patients were treated with antibiotics, and drainage of the empyema was affected by closed thoracostomy in (80.55%) of the cases. Conclusion: Empyema is not rare in our practice. Early diagnosis and proper treatment of pneumonia prevent the development of empyema. Antibiotics and tube thoracostomy is an effective method of treating pyogenic empyema thoracis in children in resource poor settings.